Superhigh-frequency characteristics of optical modulators on the basis of InGaAlAs resonance-tunnel heterostructures - Aleshkin, V. Ya (2000)
The impedance of InGaAlAs resonance-tunnel heterostructures used for modulation of optical radiation is experimentally studied in the frequency range from 45 to 18 MHz. The dependence of their equivalent circuit on the bias voltage is determined. The spectrum of the harmonics of the current in the resistive frequency multiplication in such structures is calculated. The results confirm that these structures are promising as applied to the frequency multiplication. The effect of frequency multiplication is demonstrated experimentally at low frequencies.